2011
DOI: 10.1161/hypertensionaha.111.170621
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of Severe Albuminuria in Aging Hypertensive Rats by Exchange of 2 Chromosomes in Double-Consomic Rats

Abstract: Abstract-The inherited nephron deficit and progressive albuminuria development observed in hypertensive MunichWistar Frömter (MWF) rats are influenced by quantitative trait loci on rat chromosome (RNO) 6 and RNO8. Previous studies in young MWF rats suggested that the nephron deficit represents a cause for glomerular hypertrophy preceding onset of albuminuria at 8 weeks and demonstrated a simultaneous induction of the podocyte stress marker desmin and podoplanin loss in podocytes. Key Words: genetics Ⅲ albuminu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 22 publications
3
23
0
Order By: Relevance
“…Hence, studies in the FHH, 90,93,95,97 MWF [141][142][143] and SS 53,54 rat models highlighted the role of major susceptibility loci that in concert and genetic interaction with multiple other loci influence renal disease susceptibility (Table 5). Moreover, these models allow the combination of genetic analyses with unlimited gene expression studies, 65,70,150 including timed renal and compartment-specific expression analysis during the onset of renal disease phenotypes such as albuminuria, 143,204 while these experimental algorithms are difficult or impossible to pursue in humans due to the limited access to renal tissue. The comprehensive exploitation of the genotype-renal phenotype associations that are inherited in this panel of rat strains is therefore suitable for making a significant contribution to the development of an integrated approach to the systems genetics of CKD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, studies in the FHH, 90,93,95,97 MWF [141][142][143] and SS 53,54 rat models highlighted the role of major susceptibility loci that in concert and genetic interaction with multiple other loci influence renal disease susceptibility (Table 5). Moreover, these models allow the combination of genetic analyses with unlimited gene expression studies, 65,70,150 including timed renal and compartment-specific expression analysis during the onset of renal disease phenotypes such as albuminuria, 143,204 while these experimental algorithms are difficult or impossible to pursue in humans due to the limited access to renal tissue. The comprehensive exploitation of the genotype-renal phenotype associations that are inherited in this panel of rat strains is therefore suitable for making a significant contribution to the development of an integrated approach to the systems genetics of CKD.…”
Section: Discussionmentioning
confidence: 99%
“…138,139 Recently, double-consomic studies in MWF-6 SHR 8 SHR by double transfer of SHR-RNO6 and SHR-RNO8 into MWF confirmed a strong synergistic effect between QTL on RNO6 and RNO8, since the albuminuria and associated structural kidney damage phenotypes were completely abolished in the double-consomic strain (Table 2). 143 In a reciprocal single-consomic strain, transfer of MWF-RNO8 into the isolated albuminuria-resistant SHR background caused an induction of albuminuria already under normal conditions, while an increase in structural glomerular damage was only detected after Nx in consomic SHR-8 MWF (Table 2). 144 Thus, the results demonstrate the independent role of MWF QTL on RNO8 for both albuminuria and structural kidney damage.…”
Section: Munich Wistar Frö Mter Rat Strain Breedingmentioning
confidence: 99%
“…Polygenetic recessive etiology linked to quantitative trait loci was disclosed in this strain, which was unrelated to BP regulation, 13,14 but the individual gene and related pathway have not been identified as a single factor that may underlie the pathogenesis of renal fibrosis in the MWF strain. This finding raised interest in studying whether post-transcriptional regulation of gene expression could be responsible for abnormal renal phenotype of disease progression.…”
mentioning
confidence: 86%
“…A tissues, including lymphatic endothelial cells and also podocytes [20][21][22]. Recently, PDPN was found to be upregulated in a number of different cancers and identified as a candidate cancer stem cell marker in squamous cell carcinoma [23].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, at later time points, when albuminuria had already progressed immunoelectron microscopy analysis showed that foot process effacement coincided with the loss of PDPN, whereas areas in which its expression was retained showed normal ultrastructural morphology [9]. PDPN was suggested to be involved in regulation of cell shape and foot process organization of podocytes possibly via interaction with the actin cytoskeleton [9,20,22]. However, the regulation of PDPN expression and its function in podocytes is not well characterized.…”
Section: Introductionmentioning
confidence: 99%